Changes in motivation and attitudes toward learning and cultural differences from first year to final year of studying at university among Iranian students of English, Arabic, and Russian - Hosseini, Seyed Hossein; Talebi, Seyed Hassan (Penerbit Universiti Kebangsaan Malaysia, 2015)
This paper investigates changes in attitude toward cultural differences (ethnorelativism) as well as motivation and attitudes toward learning English, Arabic and Russian from the first to the final year among the students of the respective languages at the University of Mazandaran. A group of 84 students majoring in English (42 students), Arabic (21 students) and Russian (21 students) were asked to fill out the questionnaire about the two variables (attitudes toward cultural differences as well as motivation and attitudes toward learning the foreign language they were studying). Analysis of data evinced a significant difference in attitude and motivation toward learning between first year and final year of studying at the university for Iranian students of Arabic, Russian and English. However, the Iranian learners of Arabic, unlike the Iranian learners of Russian and English, did not show any improvement from the first year to the final year on attitude toward cultural differences. It is concluded that there is no consistency among Iranian students of the three foreign languages in the two variables and that Iranian learners of English have shown most improvements in terms of motivation and attitudes toward learning English as well as attitude toward cultural differences.